HAMBATAN KERJASAMA SISTER CITYKOTA PADANG INDONESIA DAN KOTA FREMANTLE AUSTRALIA - Syarif, Nurul Alfath; Yealta, Den (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is the science of international relations that examines the effectiveness of the sister city of Padang City (Indonesia) with the City of Fremantle (Australia). This research aims to explain how the cooperative relationship between the City of Padang and the City of Fremantle, how the effectiveness of the sister city cooperation between the two cities and the obstacles that hinder the cooperation of the sister city.               The study was prepared using the international cooperation by K.J Holsti, constructivism perspective, which is then supported by nation-state analysis level. The methodology using a qualitative methode and collecting data using a library research literature.               The results of this study indicate that the sister city collaboration between the City of Padang and the City of Fremantle is less effective. This is evidenced by the absence of outputs and action plans from the collaboration as well as the many obstacles that are obstacles to the proper running of the sister city collaboration. Keyword : Cooperation, Sister City, Effectiveness, Padang City, The City of  Fremantle.